2019
DOI: 10.5194/se-10-149-2019
|View full text |Cite
|
Sign up to set email alerts
|

Tectono-thermal evolution of Oman's Mesozoic passive continental margin under the obducting Semail Ophiolite: a case study of Jebel Akhdar, Oman

Abstract: Abstract. We present a study of pressure and temperature evolution in the passive continental margin under the Oman Ophiolite using numerical basin models calibrated with thermal maturity data, fluid-inclusion thermometry, and low-temperature thermochronometry and building on the results of recent work on the tectonic evolution. Because the Oman mountains experienced only weak post-obduction overprint, they offer a unique natural laboratory for this study. Thermal maturity data from the Adam Foothills constrai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 117 publications
4
58
0
Order By: Relevance
“…The final doming of the JAD occurred from Eocene to Miocene (Hansman et al, 2017(Hansman et al, , 2018Grobe et al, 2018Grobe et al, , 2019. This process was accompanied by extensional shearing at the northern and eastern margin of the dome (Mattern and Scharf, 2018;Scharf et al, 2019), and tilting of the Arabian rocks along a WNW-ENE trending rotation axis at the northern and southern margin of the dome by ∼30° and ∼20°, respectively (compare Beurrier et al, 1986;Rabu et al, 1986).…”
Section: Shd's Neoproterozoic Formations Differ From Jad's Includingmentioning
confidence: 98%
See 1 more Smart Citation
“…The final doming of the JAD occurred from Eocene to Miocene (Hansman et al, 2017(Hansman et al, , 2018Grobe et al, 2018Grobe et al, , 2019. This process was accompanied by extensional shearing at the northern and eastern margin of the dome (Mattern and Scharf, 2018;Scharf et al, 2019), and tilting of the Arabian rocks along a WNW-ENE trending rotation axis at the northern and southern margin of the dome by ∼30° and ∼20°, respectively (compare Beurrier et al, 1986;Rabu et al, 1986).…”
Section: Shd's Neoproterozoic Formations Differ From Jad's Includingmentioning
confidence: 98%
“…Obduction was followed by extension (e.g., Fournier et al, 2006;Searle, 2007;Mattern and Scharf, 2018;Grobe et al, 2018Grobe et al, , 2019 as indicated by extensional faults, which displaced the ophiolite Searle, 2007). It is worth mentioning that both SHD and JAD display large-scale listric normal faults bounding their flanks (Searle, 2007).…”
Section: Shd's Neoproterozoic Formations Differ From Jad's Includingmentioning
confidence: 99%
“…A second shortening phase occurred during the Cenozoic and it is responsible for the deformation of the Late Cretaceous to Cenozoic post-nappe package and for the final uplift and doming of the culmination areas of the central Al-Hajar Mountains (Mount et al 1998;Breton et al 2004;Csontos et al 2010;Ali et al 2014;Cooper et al 2014;Hansman et al 2017). This uplift event was constrained by several thermochronological data (Mount et al 1998;Poupeau et al 1998;Saddiqi et al 2006;Wübbeler et al 2015;Hansman et al 2017;Grobe et al 2019) and absolute radiometric dating of veins (Grobe et al 2018;) from the Jabal Akhdar and Saih Hatat tectonic windows and surrounding areas ( Fig. 1a).…”
Section: Geological Setting Of the Al-hajar Mountainsmentioning
confidence: 98%
“…Despite this large amount of data, the timing and mode of exhumation of the main tectonic windows is still debated. Nevertheless, most recent interpretations point toward a rapid exhumation of the Jabal Akhdar Dome (Hansman et al 2017;Grobe et al 2019) starting from the early Eocene.…”
Section: Geological Setting Of the Al-hajar Mountainsmentioning
confidence: 99%
“…Image is a modified part of a rectified highresolution photograph created by Wüstefeld (2010). For the tectonic, geomechanical and pressure-temperature evolution of the area, see Grobe et al (2019). 10.1029/2019RG000671…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%